WLAN Technologies for Audio Delivery - Nicolas-Alexander Tatlas; Andreas Floros; Thomas Zarouchas; John Mourjopoulos (Advances in Multimedia)
Audio delivery and reproduction for home or professional applications may greatly benefit from the adoption of digital wireless local area network (WLAN) technologies. The most challenging aspect of such integration relates the synchronized and robust real-time streaming of multiple audio channels to multipoint receivers, for example, wireless active speakers. Here, it is shown that current WLAN solutions are susceptible to transmission errors. A detailed study of the IEEE802.11e protocol (currently under ratification) is also presented and all relevant distortions are assessed via an analytical and experimental methodology. A novel synchronization scheme is also introduced, allowing optimized playback for multiple receivers. The perceptual audio performance is assessed for both stereo and 5-channel applications based on either PCM or compressed audio signals.